Engineering a disulfide bond to stabilize the calcium-binding loop of activated protein C eliminates its anticoagulant but not its protective signaling properties - Bae, Jong-Sup; Yang, Likui; Manithody, Chandrashekhara; Rezaie, Alireza R (The Journal of biological chemistry, 2007)
In addition to an anticoagulant activity, activated protein C (APC) also exhibits anti-inflammatory and cytoprotective properties. These properties may contribute to the beneficial effect of APC in treating severe sepsis patients. A higher incidence of bleeding because of its anticoagulant function has been found to be a major drawback of APC as an effective anti-inflammatory drug. In this study, we have prepared a protein C variant in which an engineered disulfide bond between two beta-sheets stabilized the functionally critical Ca2+-binding 70-80 loop of the molecule. The 70-80 loop of this mutant no longer bound Ca2+, and the activation of the mutant by thrombin was enhanced 60-80-fold independently of thrombomodulin. The anticoagulant activity of the activated protein C mutant was nearly eliminated as determined by a plasma-based clotting assay. However, the endothelial protein C receptor- and protease-activated receptor-1-dependent protective signaling properties of the mutant were minimally altered as determined by staurosporine-induced endothelial cell apoptosis, thrombin-induced endothelial cell permeability, and tumor necrosis-alpha-mediated neutrophil adhesion and migration assays. These results suggest that the mutant lost its ability to interact with the procoagulant cofactors but not with the protective signaling molecules; thus this mutant provides an important tool for in vivo studies to examine the role of anticoagulant versus anti-inflammatory function of activated protein C.